2020
DOI: 10.1186/s41016-020-00198-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of molecular biomarkers in glioma resection: a systematic review

Abstract: New discoveries based on genetic and epigenetic evidence have significantly expanded the understanding of diffuse gliomas. Molecular biomarkers detected in diffuse gliomas are not only potential targets for radiotherapy, chemotherapy, and immunotherapy, but are also able to guide surgical treatment. Previous studies have suggested that the optimal extent of resection of diffuse gliomas varies according to the expression of specific molecular biomarkers. However, the specific guiding role of these biomarkers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Based on our previous study (14), we further demonstrated the correlation between CTC counts, IDH status, and 1p19q status of glioma. IDH and 1p19q are two of the most important molecular pathological markers of glioma, which are closely related to tumor classification and patient outcomes (23,24). We observed a remarkably lower CTC count in glioma patients with IDH mutation and 1p19q co-deletion status, which are typical features of oligodendrogliomas, suggesting that CTC count might be a good predictor for histopathological and molecular pathological diagnosis of glioma.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Based on our previous study (14), we further demonstrated the correlation between CTC counts, IDH status, and 1p19q status of glioma. IDH and 1p19q are two of the most important molecular pathological markers of glioma, which are closely related to tumor classification and patient outcomes (23,24). We observed a remarkably lower CTC count in glioma patients with IDH mutation and 1p19q co-deletion status, which are typical features of oligodendrogliomas, suggesting that CTC count might be a good predictor for histopathological and molecular pathological diagnosis of glioma.…”
Section: Discussionmentioning
confidence: 59%
“…We also observed that patients with 1p19q co-deletion status were more likely to have low CTC counts (p = 0.05). IDH and 1p19q status have important roles in the molecular diagnosis of diffused glioma (23,24). Therefore, we further investigated the correlation between CTC counts and glioma histopathology.…”
Section: Correlation Between Ctcs and Clinical Characteristics In Gli...mentioning
confidence: 99%
“…19 Consequently, many studies have reported the genomic landscape of specific H3-alterations in gliomas and their relationship with clinical characteristics and prognosis. [20][21][22] They have mainly focused on the H3.1 and H3.2 replicative histones and H3.3 and CENPA histone variants, while we tried to extend the scope to the whole histone H3 family as much as possible. We proposed that H3-alterations may cause poor outcomes and have particular clinical characteristics in patients with glioma.…”
Section: Discussionmentioning
confidence: 99%
“…It is a component of RPA but is also often poorly captured and less likely to have an immediate connection to molecular features even as it may well connect to comorbidities, another clinical facet that is poorly captured but may have a molecular signature. Additional clinical features related to the upfront management of glioma begin with the extent of resection [ 67 ]; administration of chemotherapy, in particular the extent of adjuvant temozolomide in terms of the number of cycles; and additional management upon recurrence ( Figure 2 ) for which molecular markers are not specifically identified. Figure 2 indicates clinical features with significant prognostic value for patients with glioma and current management protocols.…”
Section: Clinical and Management Features Of Significance In Gliomamentioning
confidence: 99%